The evaluation of 23-bp and 12-bp insertion/deletion within the PRNP gene and their effects on growth traits in healthy Chinese native cattle breeds. Issue 1 (1st January 2018) - Yang, Qing; Zhang, Sihuan; Liu, Liangliang; Lei, Chuzhao; Qi, Xinglei; Lin, Fengpeng; Qu, Weidong; Qi, Xingshan; Liu, Jiming; Wang, Rongmin; Chen, Hong; Lan, Xianyong
ABSTRACT: Polymorphisms in the prion protein gene (PRNP) have been linked with the occurrence of transmissible spongiform encephalopathies and the expression of some phenotypic traits in healthy animals including cattle. The aim of this study was to verify the 23-bp insertion/deletion (indel) within promoter region and the 12-bp indel within intron 1 of PRNP, as well as to evaluate their associations with growth traits. Two loci of PRNP were genotyped in 1558 healthy Chinese cattle sampled from 6 indigenous breeds. Moreover, phenotypic records for growth were used to find the relationship between PRNP polymorphisms and phenotypic performance. The results confirmed the occurrence of these two indel polymorphisms in the analysed breeds. Association analysis showed that the 23-bp indel was significantly related to the body length and heart girth in 18-months-old Nanyang cattle. The 12-bp indel was significantly related to the growth traits in three cattle breeds, such as the body weight in Xia'nan cattle, the daily gained weight in 12-months-old Nanyang cattle and the cannon circumference and rump length in Ji'an cattle. These findings indicated that these two indels may affect bovine growth traits, which could benefit to healthy cattle selection and breeding through marker-assisted selection. Abbreviations AI: artificial insemination; ANOVA: analysis of variance; Bp: base pair; BSE: bovine spongiform encephalopathy; D: deletion; DD: deletion/deletion; GLM: generalized linear model; reaction; He: heterozygosity; Ho: homozygosity; HWE: Hardy–Weinberg equilibrium; I: insertion; ID: insertion/deletion; II: insertion/insertion; Indel: insertion/deletion; MAS: marker-assisted selection; Ne: effective allele numbers; PCR: polymerase chain reaction; PIC: polymorphism information content; PrP: Prion protein (PrP); PRNP : the prion protein; RP58: repressor protein with a predicted molecular mass of 58 kDa; SNP: single nucleotide polymorphism; Sp1: specific protein 1; SPSS: statistical product and service solutions; TSE: transmissible spongiform encephalopathies